Reversible phase transformation in Ti2AlC films during He radiation and subsequent annealing. Issue 13 (October 2021) - Su, Ranran; Zhang, Hongliang; Liu, Longfei; Shi, Liqun; Wen, Haiming
Abstract: Ti2 AlC film can be used as a protective coating for fuel cladding materials and structural materials in nuclear reactors. However, the related radiation damage and the helium (He) effects have not been well understood. In this work, the He radiation effects on Ti2 AlC thin films, deposited by reactive magnetron sputtering, were studied. In addition to the detailed characterization of the radiation-induced defects and He bubbles, phase transformation was identified and investigated during film deposition, ion irradiation, and subsequent annealing. Results suggested that the hexagonal close-packed (hcp) Ti2 AlC was formed from a solid-solution face-centered cubic (fcc) (Ti2 Al)C phase during the film deposition process. A phase transformation from hcp-Ti2 AlC to fcc-(Ti2 Al)C happened during the He ion irradiation, while a reversible phase transformation from fcc-(Ti2 Al)C to hcp-Ti2 AlC occurred during the post annealings at temperatures above 600 °C. The reversible phase transformation indicates dynamic restoration of this material and provides insights into the design of new irradiation-damage-tolerant ceramic materials.